The different levels of creative attitudes versus social competences and coping with stress style among academic youth - Małkiewicz, Monika M.; Piskozub, Mirosław (Studia Psychologica: Theoria et praxis, 2011)
The aim of the study was to investigate the relationship between different intensity of creative attitudes and the level of social competences and coping with stress style among first-year students. The theoretical basis was the Stanislaw Popek Theory of Creative Attitudes, Anna Matczak Theory of Social Competences and N.S. Endler and J.D. Parker Theory of Coping with Stress Style. There were 130 students evaluated by Creative Behaviour Questionnaire KANH by S. Popek, Social Competences Inventory KKS by A. Matczak and Stress Coping Strategies Questionnaire CISS by N.S. Endler and J.D. Parker, in Polish adaptation by Szczepaniak, Wrześniewski. It was found that, there are differences in social competence levels and coping style among participants with different intensity of creative attitude. In general, creative people have higher social skills than the people with imitative attitudes. They have higher scores in KKS Inventory than once with imitative attitudes in the following scales: social exposure situations behavior (ES), situations requiring assertive behavior (A) and in the overall result (WL). Also people with medium intensity of creativity have higher social competences than those with imitative attitudes. Participants with creative attitudes are more problems oriented than people with imitative attitudes and with medium level of creativity. They also have lower scores in CISS Questionnaire, in scales: emotion-focused coping, avoidance-focused coping, including involving into substitute activities, like watching TV or playing computer games.